Case Report: Budd–Chiari-like syndrome in a cat with polycystic kidney and liver disease - Lee, Eun-Soo; Jang, Yoon-Seok; Han, Jae-Il; Kim, Tae-Rin; Kim, Jae-Hwan; Hyun, Jae-Eun (Frontiers in Veterinary Science, 2026)
A 9-year-old spayed female Persian Chinchilla cat presented with progressive lethargy and acute right hindlimb pain and lameness. Diagnostic imaging revealed diffuse renal and hepatic cysts, resulting in marked hepatomegaly. Computed tomography (CT) further identified a localized narrowing of the intrahepatic caudal vena cava (CVC), likely due to extrinsic compression by the enlarged liver. Laboratory tests revealed moderate anemia, leukocytosis, hypoalbuminemia, and a hypercoagulable state with markedly elevated serum amyloid A levels. Based on these findings, the cat was diagnosed with polycystic kidney and liver disease (PKD/PLD), complicated by Budd–Chiari-like syndrome (BCLS), a rare hemodynamic disorder in felines. Despite supportive care, the patient succumbed to renal failure within 7 weeks. Whole-genome sequencing identified a heterozygous known pathogenic non-sense mutation in PKD1 (XM_023247051.2:c.9864C > A), a novel frameshift mutation in GANAB, and multiple missense variants in PKD1 and PKHD1. To the best of our knowledge, this is the first reported case of feline BCLS secondary to PLD-induced CVC compression. These findings underscore the importance of considering vascular complications in advanced PKD/PLD and suggest that multigenic variation may contribute to disease severity and clinical variability.